Evaluation of surgical treatment for incidental gallbladder carcinoma diagnosed during or after laparoscopic cholecystectomy: single center results. (December 2017) - Utsumi, Masashi; Aoki, Hideki; Kunitomo, Tomoyoshi; Mushiake, Yutaka; Yasuhara, Isao; Arata, Takashi; Katsuda, Koh; Tanakaya, Kohji; Takeuchi, Hitoshi
Abstract Background Laparoscopic cholecystectomy (LC) is the accepted standard management for benign gallbladder disease. LC rarely results in a diagnosis of incidental gallbladder carcinoma (IGBC). The aim of our study was to report our experience with IGBC diagnosed during or following LC. Methods Between January 2008 and January 2015, 352 patients underwent LC at Iwakuni Clinical Center. Among these patients, 8 (2.3%) were diagnosed with IGBC. We evaluated their characteristics, surgical related variables, histopathological findings and surgical outcomes. Results Patient median age was 71 (range 49–88) years, and 3 out of 8 were female. All patients with IGBC were Japanese. The grade of cancer was as follows: pT1a (3 cases), pT2 (4 cases) and pT3 (1 case). Two patients with pT2 disease underwent radical surgery. The median follow-up time of these patients was 24 (range 11–80) months. All patients are still alive and two of three patients who refused radical surgery have developed recurrence (liver metastases and recurrence in the peritoneum). Conclusions Although the number of cases was small, the results of this study further support the suggestion that gallbladder carcinoma may be curable if diagnosed as IGBC at an early stage. If the cancer has reached an advanced stage, radical surgery should be performed.